Bacterial Resistance Toward Antimicrobial Ionic Liquids Mediated by Multidrug Efflux Pumps - Gundolf, Tobias; Kalb, Roland; Rossmanith, Peter; Mester, Patrick (Frontiers in Microbiology, 2022)
The effective elimination of foodborne pathogens through cleaning and disinfection measures is of great importance to the food processing industry. As food producers rely heavily on disinfectants to control pathogenic bacteria in their facilities, the increasing spread of tolerant, often even multidrug resistant, strains is of particular concern. In addition to efforts to prevent or at least reduce development and spread of strains tolerant to disinfectants and sanitizers, there is an urgent need for new and effective antimicrobials. One new class of promising antimicrobials are ionic liquids (ILs), which have been reported to be effective against resistant strains as they interact with bacterial cells in multiple ways, but investigations of their effectivity against MDR bacteria or specific defense mechanisms are still limited. This study investigates the role of multidrug efflux pumps of the Resistance Nodulation-Division family (RND) on the resistance of bacterial pathogens Escherichia coli and Salmonella enterica serovar Typhimurium towards ten antimicrobial active ILs. Results reveal that, while known structure-activity relationships (SARs), such as the side-chain effect, were found for all strains, antimicrobial ILs with one elongated alkyl side-chain were significantly affected by the RND efflux pump, highlighting the importance of efflux pumps for future IL toxicity studies. In case of antimicrobial ILs with multiple side-chains and different cationic head groups, two ILs were identified that were highly active against all investigated strains with little to no effect of the efflux pump. Based on this study it is possible to identify and design antimicrobial ILs as effective biocides against MDR bacteria that can be further optimized as new disinfectants.